2016
DOI: 10.1038/srep33789
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Neutrophil to Lymphocyte Ratio in Oncologic Outcomes of Cholangiocarcinoma: A Meta-analysis

Abstract: Increasing evidence indicates that the neutrophil to lymphocyte ratio (NLR) is a useful biomarker of long-term outcomes in patients with cholangiocarcinoma. However, the prognostic role of NLR in patients with cholangiocarcinoma remains unclear. Thus, the current meta-analysis was undertaken to clarify the correlation between NLR and overall survival (OS) in cholangiocarcinoma, and a comprehensive literature research was conducted to understand the association of NLR and prognosis of cholangiocarcinoma. The ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…A recent meta-analysis demonstrated that a high NLR was significantly associated with poor OS in patients with cholangiocarcinoma [14]. In addition, several studies demonstrated a significant correlation between GPS/modified GPS and the survival of patients with extrahepatic bile duct cancer following surgical resection [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis demonstrated that a high NLR was significantly associated with poor OS in patients with cholangiocarcinoma [14]. In addition, several studies demonstrated a significant correlation between GPS/modified GPS and the survival of patients with extrahepatic bile duct cancer following surgical resection [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil counts, lymphocyte counts, platelet counts, elevated C-reactive protein (CRP) levels, and hypoalbuminemia have been converted to ratios or scores, such as the neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR), and Glasgow Prognostic Score (GPS) [6], which have frequently been associated with the prognosis of solid tumors [5-7]. However, there are conflicting survival data regarding preoperative hematological inflammatory parameters in cholangiocarcinoma [8-14]. …”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil‐to‐lymphocyte ratio (NLR) is defined as the absolute neutrophil count divided by the absolute lymphocyte count, and it is a readily measurable marker of systemic inflammation. Its association with survival outcomes for various types of cancer, including head and neck squamous cell carcinoma, has been demonstrated previously . Nevertheless, the association of the NLR and anemia with either the response to induction chemotherapy or with treatment outcomes in laryngeal‐preservation protocols has not been reported to date, and we hypothesized that both associations were significant.…”
Section: Introductionmentioning
confidence: 78%
“…Its association with survival outcomes for various types of cancer, including head and neck squamous cell carcinoma, has been demonstrated previously. 5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Nevertheless, the association of the NLR and anemia with either the response to induction chemotherapy or with treatment outcomes in laryngeal-preservation protocols has not been reported to date, and we hypothesized that both associations were significant. The aim of the present study was to determine the prognostic value of the NLR and anemia in patients treated with a laryngeal preservation protocol for laryngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A chi‐square test, Fisher's exact test, and Student's t test were used for comparisons between groups as appropriate. Neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) was calculated as follows: NLR = absolute neutrophil count/absolute lymphocyte count ; PLR = absolute platelet count/absolute lymphocyte count . Cox proportional hazard regression model was used to determine prognostic factors.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%